Cognitive Differences and the Coding Analysis of the Interaction Behavior Patterns in the Innovation Team - Zhao, Yan; Gui, Huangyi; Hu, Tianjiao; Xu, Ke (Frontiers in Psychology, 2022)
To explore the difference in the interaction behavior patterns of members caused by the cognitive differences in the higher and lower innovation-performing teams and provide suggestions for effective interaction in innovation teams, this study adopts the “Input-Process-Output” theoretical framework and an innovation experiment was conducted in 12 innovation teams based on an experimental paradigm proposed for team innovation tasks after improvement. Subsequently, team members’ 1754 behaviors were coded to analyze the similarities and differences of the behavior patterns between higher and lower innovative-performing teams with lag sequential analysis. The results revealed that both higher and lower innovative-performing teams showed the same interaction behavior patterns. More specifically, the probability of idea facilitation behavior being followed by team spirit facilitation behavior was significantly higher than expected, while the probability of idea facilitation behavior recurring after idea facilitation behavior was significantly lower than expected. However, in lower innovative-performing teams, there were some special interaction behavior patterns, such as “the probability of idea facilitation behavior being followed by neutral interaction or idea inhibition behavior was significantly lower than expected”. These phenomena may reflect some realistic situation in our life, such as “One echoes the other”, “Sit on the sidelines” and “A gentleman is ready to die for his bosom friends” in the members’ interaction after cognitive differences happen. This paper provides opinions and suggestions for the research on the interaction behavior observation and coding analysis among members of innovation teams and has theoretical contributions to the research on the behavior observation of innovation teams.